Interdisciplinary connections to special education important aspects to consider - Bakken, Jeffrey P.; Obiakor, Festus E. (Bingley, U.K. : Emerald, 2015)
This two-part volume addresses the specific area of interdisciplinary connections within special education research. Special education has transformed as a result of legislation, new trends and current research investigations. Currently, there is no comprehensive resource that effectively covers these advances. Part A sets the agenda for this two-part volume by addressing the challenge of why an interdisciplinary understanding is necessary and also outlines the benefits of adopting a multidisciplinary framework.
Rationale for interdisciplinary/multidisciplinary relations in special education / Jeffrey P. Bakken -- The role of special educators in interdisciplinary connections / Tachelle Banks -- Role of general educators in a multidisciplinary team for learners with special needs / D. Antonio Cantu -- Role of counselors in multidisciplinary interactions in special education / Beto Davison Avile<U+0301>s, Lori Russell-Chapin, Christopher J. Rybak -- Role of psychologists in interdisciplinary relations in special education / Lynda Kasky-Herna<U+0301>ndez, Gary Cates -- Role of school leaders in interdisciplinary connections in special education / D. Michael Risen, Jenny Tripses, Anne Risen -- Roles of related professionals in special education / Stacey Jones Bock, Christy Borders -- Role of parents/families/guardians / Julia Stoner -- The role of community in special education : a relational approach / Kate Warner, Karla Hull, Martha Laughlin -- Role of government agencies in enhancing special education / Sunday Obi -- Different roles and similar mission in the education of students with special needs : the comprehensive support model at work / Festus E. Obiakor, Michael Afolayan, Pauline Harris-Obiakor, Precious Afolayan.
Print version record
Keywords: Education -- Special Education -- General; Teaching of specific groups & persons with special educational needs; Special education; Interdisciplinary approach in education